ANALISIS PENGGUNAAN ASESMEN FORMATIF DALAM PEMBELAJARAN ANAK USIA DINI DI TK SWASTA PLUS ULUL ILMI ISLAMIC SCHOOL MEDAN MARELAN TAHUN AJARAN 2023/2024 - Yayang Zahra Salsabilah; Anita Yus (CV. ADIBA ASIHA AMIRA, 2024)
Assessment in early childhood education is divided into two types: formative assessment and summative assessment. Formative assessment helps evaluate ongoing learning, while summative assessment provides an overview of the final achievements of students during the learning process, which can be used for evaluative decision-making. This research focuses on formative assessment with the aim of analyzing its use in early childhood education at TK Swasta Plus Ulul Ilmi Islamic School in Medan Marelan. The method used in this study is descriptive qualitative research. The research was conducted from July 2024 to September 2024. The data sources in this study were three teachers from TK Swasta Plus Ulul Ilmi Islamic School Medan Marelan. The data collection techniques used were observation, interviews, and documentation. Data analysis was carried out using Miles and Huberman's data analysis stages: data reduction, data presentation, and conclusion drawing. Data validity was tested through triangulation. The results showed that the use of formative assessment in early childhood education at TK Swasta Plus Ulul Ilmi Islamic School Medan Marelan has been implemented fairly well. Four types of assessment instruments were used: anecdotal notes, checklists, series of photos, and student work. Data collection was also carried out through observation, performance tes, and portfolios